Collecting more than half the fluorescence photons from a single ion - Maiwald, Robert; Golla, Andrea; Fischer, Martin; Bader, Marianne; Heugel, Simon Tobias; Chalopin, Benoit; Sondermann, Markus; Leuchs, Gerd (Physical Review A, 2012)
We demonstrate the trapping of a single ion in the focus of a deep parabolic mirror that covers 81% of the solid angle surrounding the ion. Accounting for the reflectivity of the mirror we infer a photon collection efficiency of 54.8% for our setup. The underlying experimentally detected maximum fluorescence rate is 1.91×106 s 1 from a single 174Yb ion, mainly limited by the quantum efficiency of our photon detector. Besides the high collection efficiency, the integration of an ion trap into a parabolic mirror is a key ingredient for efficient coupling of light to a single ion in free space. © 2012 American Physical Society.

Efficient saturation of an ion in free space - Fischer, Martin; Bader, Marianne; Maiwald, Robert; Golla, Andrea; Sondermann, Markus; Leuchs, Gerd (Applied Physics B-Lasers and Optics, 2014)
We report on the demonstration of a light-matter interface coupling light to a single (Formula presented.) ion in free space. The interface is realized through a parabolic mirror partially surrounding the ion. It transforms a Laguerre–Gaussian beam into a linear dipole wave converging at the mirror’s focus. By measuring the non-linear response of the atomic transition, we deduce the power required for reaching an upper-level population of (Formula presented.) to be (Formula presented.) at half linewidth detuning from the atomic resonance. Performing this measurement while scanning the ion through the focus provides a map of the focal intensity distribution. From the measured power, we infer a coupling efficiency of (Formula presented.) on the linear dipole transition when illuminating from half solid angle, being among the best coupling efficiencies reported for a single atom in free space.

Focusing characteristics of a 4pi parabolic mirror light-matter interface - Alber, Lucas; Fischer, Martin; Bader, Marianne; Mantel, Klaus; Sondermann, Markus; Leuchs, Gerd (arXiv, 2016)

Focusing characteristics of a 4π parabolic mirror light-matter interface - Alber, Lucas; Fischer, Martin; Bader, Marianne; Mantel, Klaus; Sondermann, Markus; Leuchs, Gerd (Journal of the European Optical Society: Rapid Publications, 2017)

Measuring the temperature and heating rate of a single ion by imaging - Srivathsan, Bharath; Fischer, Martin; Alber, Lucas; Weber, Markus; Sondermann, Markus; Leuchs, Gerd (New Journal of Physics, 2019)

Prospects of Trapping Atoms with an Optical Dipole Trap in a Deep Parabolic Mirror for Light-Matter-Interaction Experiments - Sondermann, Markus; Fischer, Martin; Leuchs, Gerd (Advanced Quantum Technologies, 2020)
Keywords: light-matter interaction; optical trapping; parabolic mirror

Resonant photo-ionization of Yb+ to Yb2+ - Heugel, Simon Tobias; Fischer, Martin; Elman, Vladimir; Maiwald, Robert; Sondermann, Markus; Leuchs, Gerd (Journal of Physics B: Atomic, Molecular and Optical Physics, 2016)
We demonstrate the controlled creation of a Yb ion by photo-ionizing Yb with weak continuous-wave lasers at ultraviolet wavelengths. The photo-ionization is performed by resonantly exciting transitions of the Yb ion in three steps. Starting from an ion crystal of two laser-cooled Yb ions localized in a radio-frequency trap, the verification of the ionization process is performed by characterizing the properties of the resulting mixed-species ion-crystal. The obtained results facilitate fundamental studies of physics involving Yb ions.
Keywords: light-matter interaction; photo-ionization; ytterbium

Shifting the phase of a coherent beam with a 174Yb+ ion: influence of the scattering cross section - Fischer, Martin; Srivathsan, Bharath; Alber, Lucas; Weber, Markus; Sondermann, Markus; Leuchs, Gerd (Applied Physics B-Lasers and Optics, 2017)
We discuss and measure the phase shift imposed onto a radially polarized light beam when focusing it onto an Yb ion. In the derivation of the expected phase shifts, we include the properties of the involved atomic levels. Furthermore, we emphasize the importance of the scattering cross section and its relation to the efficiency for coupling the focused light to an atom. The phase shifts found in the experiment are compatible with the expected ones when accounting for known deficiencies of the focusing optics and the motion of the trapped ion at the Doppler limit of laser cooling (Hänsch and Schawlow in Opt Commun 13:68–69, 1975).